2020
DOI: 10.1007/s00442-020-04656-2
|View full text |Cite
|
Sign up to set email alerts
|

Post-dispersal factors influence recruitment patterns but do not override the importance of seed limitation in populations of a native thistle

Abstract: Whether plant populations are limited by seed or microsite availability is a long-standing debate. However, since both can be important, increasing emphasis is placed on disentangling their relative importance and how they vary through space and time. Although uncommon, seed addition studies that include multiple levels of seed augmentation, and follow plants through to the adult stage, are critical to achieving this goal. Such data are also vital to understanding when biotic pressures, such as herbivory, infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…This phenomenon, i.e. spatial variation in the factors limiting plant populations can modulate treatment effects on plant population dynamics, was also shown by Rand et al [ 53 ]. Thus, strategies for population management may have to pay attention to specific site conditions.…”
Section: Discussionsupporting
confidence: 59%
“…This phenomenon, i.e. spatial variation in the factors limiting plant populations can modulate treatment effects on plant population dynamics, was also shown by Rand et al [ 53 ]. Thus, strategies for population management may have to pay attention to specific site conditions.…”
Section: Discussionsupporting
confidence: 59%
“…Life history tradeoffs link the two feedback loops, as both acquisitive traits associated with fast growth under favorable conditions (e.g., photosynthetic rates, SLA) and traits associated with fecundity and dispersal (e.g., seed size) have been found to trade off with the ability to survive in the shade in tropical forests (Lai et al, 2021;Turner, 2008) (but see Clark et al, 2004). That implies that, because we analyzed sapling recruitment rather than seed dispersal, the pattern of increasing CWM seed mass may reflect that larger-seeded species became less dispersal limited, but also that decreasing light levels increasingly limit seedling establishment and survival of smallerseeded species (Gratzer et al, 2022;Kraft et al, 2015;Rand et al, 2020). An earlier trait-based study in our field site provides support for the latter, showing that maximum photosynthesis was a better predictor of successional changes in species' recruitment and mortality rates than seed mass (Lai et al, 2021).…”
Section: The Role Of Dispersal Limitation In Successional Feedback Dy...mentioning
confidence: 99%
“…For instance, seed transport associated with flooding patterns might augment propagule pressure and shorten timelines for Russian olive ( Elaeagnus angustifolia L.) stand increase (West et al 2020). Rand et al (2020) demonstrated seed predation by a biological control agent reduces already limited seed availability, further reducing populations of a non-target thistle ( Cirsium canescens Nutt. ), even when recruitment pressures differ across sites.…”
Section: Present—ars Weed Science Researchmentioning
confidence: 99%